Pengaruh Personal Branding dan Content Marketing Terhadap Customer Engagement - Petra Juliana Bella; Vina Meliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
The impact of easy access to the internet by society has resulted in rapid technological developments. One of the advantages of the advancement of the internet and social media is its ability as a platform to promote tourist attractions through social networks, as well as utilizing media to disseminate marketing content and build unique identities as part of personal branding, a routine commonly carried out by public figures. One of the influential public figures through the TikTok platform is Pranichia. The data collection method for this research uses an online questionnaire via Google Form with a Likert Scale. This research is a type of quantitative research that uses non-probability sampling, especially purposive sampling, and the data is analyzed using SPSS. The research results show that the independent variables Personal Branding (X1) and Content Marketing (X2) are related to the dependent variable, Customer Engagement (Y). To find out how much influence the independent variable has on the dependent variable.